A new species of Trichogramma Westwood (Hymenoptera: Trichogrammatidae) closely related to T. chilonis Ishii from Pakistan - Nasir, Farooq Muhammad; Büttner, Carmen; Reichmuth, Christoph; Poswal, Ashraf; Hagedorn, Gregor; Schöller, Matthias (Zootaxa, 2011)
A new species of Trichogramma Westwood (1833) (Hymenoptera: Trichogrammatidae) parasitizing eggs of Helicoverpa armigera (Hübner, 1808) (Lepidoptera: Noctuidae) on tomato in Northern Punjab, Murree hills, Pakistan is described. The new species is closely related to T. chilonis Ishii, the most widely distributed species in Pakistan and India. Morphological characters, ITS-2 sequence differences and reproductive data are presented to distinguish T. siddiqi n. sp. from T. chilonis.